Job Satisfaction and its Influencing Factors among Shomal Health Center of Tehran Personnel in 2014 - Mohammad-Hossein Safi; Sharif Torkaman-nejad; Shahnam Arshi (Shahid Beheshti University of Medical Sciences, 2016)
Background and Objective: Job satisfaction is an important variable in the area of organizational behavior. Without job satisfaction it is not possible to achieve organizational goals. Therefore the purpose of this study was to assess job satisfaction among Shomal health center of Tehran personnel affiliated to Shahid Beheshti University of Medical Sciences. Materials and Methods: This cross- sectional study was a descriptive-analytical one. Shomal health center of Tehran personnel with at least six months of work experience participated in the study. Data were collected by demographic characteristics and the Minnesota Satisfaction questionnaire. Job satisfaction was categorized into six areas and five levels. Reliability of the questionnaire was confirmed through Chronbach's alpha calculation. Statistical analysis was conducted using SPSS-18 software. Results: Two hundreds and Fifty-nine personnel participated in the study. The mean (SD) of overall satisfaction score was 50.1(12.3) from 100. The study showed that job satisfaction of financial facilities and welfare, educational facilities and job promotion, politics and policy management, quality of human relations, Job security and professional social status were 40%, 43.4%, 53.4%, 66.6%, 54.3% and 57.4%, respectively. Statistical analysis showed a significant relationship between gender and occupational field. Conclusion: Improving the physical conditions at workplace, increasing employee participation in decision-making, the relative increase in salary, Encouraging personnel, job promotion and intimate relationships between them can lead to increase job satisfaction among employees.